"Can You Hear Me Now … ?" What the New Physical Education Acoustic Standard Means to You and Your Students. Issue 1 (2nd January 2022) - Ryan, Stu; van der Mars, Hans
Abstract : The purpose of this article is to introduce the new "Acoustic Standard for Physical Education Teaching Environments ANSI/ASA S12.60-2019/Part 4" and share the research evidence that formed the basis for developing this physical education-specific standard, provide an overview of how the standard was developed, and offer practical suggestions for physical educators in how this standard can be used at times when school districts are planning the construction of new school buildings.